Analisis Profitabilitas dan Likuiditas dalam Menilai Kinerja Keuangan PT Wilmar Cahaya Indonesia, TBK Tahun 2019-2023 - Nadia Gustia Fitri; Sihabudin; Robby Fauji (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the performance of companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 using Profitability and Liquidity financial ratio analysis. The type of research used is Descriptive Quantitative data used in the form of numbers or qualitative data arranged in the form of numbers. Data and Information are obtained from the Indonesia Stock Exchange. Based on the Liquidity ratio, it has increased every year so that the company is categorized as being in good condition, while based on Profitability, it shows a decline so that it can be said that the company is in poor condition